Job Satisfaction Overview Among Employees in a Telecommunications Company: Gambaran Kepuasan Kerja di Kalangan Karyawan di Perusahaan Telekomunikasi - Dimmas Wahyu Saputra; Lely Ika Maryati (Academia Open, 2023)
General background, job satisfaction significantly impacts employee performance and organizational success. Specific background, recent observations show dissatisfaction among some employees, highlighting the need for further research. The knowledge gap lies in the lack of specific data on job satisfaction at this company. The aim is to describe employee satisfaction and the factors contributing to it. Using a descriptive quantitative method, data were collected from 165 employees. Results showed 55.8% were satisfied, 32.1% very satisfied, and 6.1% dissatisfied. The novelty lies in analyzing satisfaction across psychological, physical, social, and financial factors. The implications suggest improvements in employee welfare and organizational policies to address areas of dissatisfaction. Highlights: High Satisfaction: Majority of employees (55.8%) are satisfied with their jobs. Dissatisfaction Present: 6.1% of employees reported dissatisfaction, requiring attention. Key Factors: Satisfaction was influenced by psychological, physical, social, and financial aspects. Keywords : Job Satisfaction, Employee Performance, Organizational Success, Workers